Má měnový agregát M3 vliv na inflaci? Případová studie České republiky, Švýcarska a Izraele - Černohorská, Liběna; Maléř, Petr (University of Pardubice, 2019)
The aim of the paper is to analyse the influence of monetary aggregate M3 on inflation in the Czech Republic, Switzerland and Israel between the years 2000 and 2017. The central banks in selected countries have not been able to fulfill their stated goal of achieving price stability. During the period under review, the selected central banks chose foreign exchange intervention as an instrument of unconventional monetary policy to achieve the set inflation target. The analysis of monetary policy in the selected countries will be determined by the long-term relationships between the M3 monetary aggregate and the inflation. Selected indicators were analyzed on quarterly data in the Czech Republic, Switzerland and Israel using the Engle - Granger cointegration test. We have found, based on the tests performed, that monetary policy in the monitored countries was not quite effective in the years 2000- 2017 because we did not confirm in our empirical analyzes the long-term relationship between the monetary aggregate M3 in relation to inflation.
Does the monetary aggregate M3 the affect on the inflation? A case study of the Czech republic, Switzerland and Israel
Keywords: Engle-Granger test; foreign exchange intervention; inflation; monetary policy; M3; E51; E47; C32; O24